Pemanfaatan Platform Belajar Online Pada Mahasiswa PGSD Universitas Muhamaddiyah Makassar Terhadap Tantangan Fenomena Sosial - N, Nurusiah; S, Syamsuriyanti; N, Nursalam (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research explores the use of online learning platforms by students of the Primary School Teacher Education Study Program (PGSD) at Muhammadiyah University of Makassar and its impact on social phenomena. Mixed quantitative and qualitative methods were used, with the survey focused on 22 students. The results show that the majority of students (40%) believe that online learning platforms have a positive impact on understanding the material. Additionally, 24% of students see increased social interaction, while 40% appreciate time flexibility. Despite the benefits, technical challenges (9%) and adaptation difficulties (16%) remain barriers. Limited internet access (75%) is in focus, highlighting the importance of adequate technological infrastructure. It found that 40% of students developed virtual social skills, but 16% felt the lack of face-to-face interaction affected the quality of learning. Economic challenges (9%) and limited device access (11%) were also identified. The importance of independent learning is reflected by 40% of students who feel it, and online assignments are considered to increase engagement (40%). Despite the benefits, 11% of students experienced increased academic stress. Social media integration was assessed positively by 40% of students.Â